PENGARUH DUE PROFESSIONAL CARE, AKUNTABILITAS, KOMPLEKSITAS DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDITPADA KANTOR BPKP PROVINSI SUMATERA UTARA - Ester Zebua; Dertina Eftaria Munthe; Dinda Wulan Sari; Vitri Sari Naibaho; Tetty Tiurma Uli Sipahutar (Jurnal Akrab Juara, 2019)
This study conducted to determine the effect of due professional care, accountability, the complexity of the audit, and time budget pressure on audit quality in BPKP of Sumatera Utara. Source of data in this study are primary data in the form of answer to the questionnaire to the auditor BPKP in Sumatera Utara and secondary data in the form of the number of auditors BPKP in Sumatera Utara. Method of determining the sampel in this study using purposive sampling method and the method that meets the criteria as much as 90 samples. Data analisystechinques in this study using multiple linear regression analisys, where the result showed a variable due professional care, accountability, and time budget pressure positive effect on audit quality, while the variable complexity of the audit negatively effect audit quality.